DISRUPSI POLITIK: STRATEGI MARKETING POLITIK MENGGUNAKAN TEKNOLOGI INFORMASI DAN KOMUNIKASI TERHADAP GENERASI MILENIAL DAN GEN Z DI PILPRES 2024 - Tandung, Chrisley Silambi; Brasit, Nurdin; Yusuf, Ria Mardiana (Journal of Risk and Uncertainty Issues, 2023)
Disruption is indeed unavoidable, especially in facing the Presidential and Vice Presidential elections of the Republic of Indonesia for the 2024-2029 period. One clear disruption observed in these activities is the emergence of the presidential and vice presidential candidates, where the vice presidential candidate must first seek approval from the Constitutional Court due to the age of the candidate, Gibran Rakabuming Raka, not yet reaching 40 years old as required by Law Number 7 of 2017 concerning General Elections, which stipulates a minimum age of 40 (forty) years or having held a position elected through general elections, including regional heads. In this case, the Constitutional Court granted the lawsuit Number 90/PUU-XXI/2023 against article 169 letter q of Law Number 7 of 2017 concerning General Elections and cleared Gibran Rakabuming Raka as the vice presidential candidate to accompany Prabowo as the Presidential Candidate of the Republic of Indonesia for the period 2024-2029. One of the reasons behind the emergence of vice presidential candidate Gibran Rakabuming Raka is the disagreement among the party chairpersons within the Koalisi Indonesia Maju (KIM) in determining Prabowo Subianto's vice presidential companion as the presidential candidate endorsed by the Koalisi Indonesia Maju. Koalisi Indonesia Maju consists of 9 parties including Gerindra, Golkar Party, Partai Bulan Bintang (PBB), Democratic Party, Partai Amanat Nasional (PAN), Garuda Party, Partai Solidaritas Indonesia (PSI), Gelora Party, and Prima Party. This underlies why Gibran Rakabuming Raka's name emerged as the sole candidate for Vice President to accompany Prabowo Subianto as the presidential candidate. Young people, particularly millennials and Gen Z often referred to as Agents of Change, dominate nearly 60% of the electorate and play a crucial role in this era to support the success of political parties. Why is disruption closely related to millennials, Gen Z, and the 2024 presidential election? Because in the 2024 presidential election, disruption could potentially strip the roles of political parties if they refuse to follow the disruption trend (engaging with digital media that suits the preferences of millennials and Gen Z). There will be competition among political parties to vie for the votes of the people in the 2024 presidential election. By integrating various opinions and survey results, it can be understood that the 2024 presidential election presents a significant opportunity for political parties to secure top positions in the race for public votes through various political marketing disruption opportunities, provided they have suitable strategies to attract interest, enhance branding, mobilize masses through social media campaigning, and deliver logical reasoning according to the perspectives of millennials and Gen Z.